2009
DOI: 10.1029/2008gl036544
|View full text |Cite
|
Sign up to set email alerts
|

Disaggregation of GOES land surface temperatures using surface emissivity

Abstract: [1] Accurate temporal and spatial estimation of land surface temperatures (LST) is important for modeling the hydrological cycle at field to global scales because LSTs can improve estimates of soil moisture and evapotranspiration. Using remote sensing satellites, accurate LSTs could be routine, but unfortunately the only instruments available to provide diurnal cycle observations have coarse spatial resolution (4 km). One approach that may help overcome the spatial resolution constraint is to disaggregate geos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
42
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 14 publications
0
42
0
1
Order By: Relevance
“…The authors found that the emissivity-based approach was more 3 accurate than a similar one based on NDVI. Note that the approach of Inamdar and French (2009) is not applicable to the disaggregation of MODIS type data over agricultural areas. The rationale is that agricultural covers evolve quickly and surface changes drastically between two successive ASTER emissivity products separated by a minimum of 16 days and more often (clouds, programming requests) by several months.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors found that the emissivity-based approach was more 3 accurate than a similar one based on NDVI. Note that the approach of Inamdar and French (2009) is not applicable to the disaggregation of MODIS type data over agricultural areas. The rationale is that agricultural covers evolve quickly and surface changes drastically between two successive ASTER emissivity products separated by a minimum of 16 days and more often (clouds, programming requests) by several months.…”
Section: Introductionmentioning
confidence: 99%
“…Although the NDVI-based approach has been successfully tested over agricultural areas, Agam et al (2007) and Inamdar et al (2008) emphasized the limitation that the variability of surface temperature is not explained entirely by NDVI. Recently, Inamdar and French (2009) developed a new disaggregation methodology of 5 km resolution GOES data using 1 km resolution MODIS-derived surface emissivity. The authors found that the emissivity-based approach was more 3 accurate than a similar one based on NDVI.…”
Section: Introductionmentioning
confidence: 99%
“…The employed empirical model can be linear or nonlinear [12,13] depending mostly on the type and number of LST predictors employed (for downscaling TIR DN or radiances, the nonlinear factors of the atmospheric and emissivity effects should also be taken into consideration during this selection [12]). Zhan et al [11] discuss that simple tools such as linear and quadratic tools are effective when the predictors' number is low (e.g., [9,10,16,17]), while complex tools such as support vector regression machines (SVM) are better suited when multiple LST predictors are employed (e.g., [18][19][20]). In principle, the LST is determined by numerous factors, including topography, vegetation abundance and vigor, soil moisture, land cover and meteorological conditions [16]; and usually the relationship between the LST data and the LST predictors is nonlinear [13].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Kustas et al [9] utilized the NDVI with a quadratic regression tool (this method is referred in literature as disTrad: disaggregation procedure for radiometric surface temperature), whereas Agam et al [10] used the fractional vegetation cover with a linear tool and also other variants of disTrad. Inamdar et al [16] employed the emissivity for downscaling GOES (Geostationary Environmental Satellite) LST data, while Essa et al [26] expanded the disTrad methodology and tested 15 remote sensing based indices (individually) as LST predictors (including soil, vegetation and built-up indices). Stathopoulou and Cartalis [8] enhanced the spatial resolution of AVHHR (Advanced Very High Resolution Radiometer) LST data using as LST predictors the effective emissivity and a LST map retrieved from Landsat 5 data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation